KOMUNIKASI YANG EFEKTIF DALAM PENDIDIKAN KARAKTER - Nisa, Hoirun (UNIVERSUM, 2016)
Communication becomes a system in a process of character education. It means that character education is influenced by the quality of built communication. An effective communication has rules, requirements, principles and universal strategies so that now the existence is significant enough to be implemented in character education. Various model of communication which come from either Al-Qur’an and Hadist or from thought of communication experts, depend on the educators’ quality in putting their function and responsibility. This article discusses that problem by analyzing model and form of modern communication, combining with the communication principles in Al-Qur’an and Hadits, and its relation with character education. The result shows that educator factor becomes the dominant factor in character education.Keywords; Modern communication, Islamic concept, Character education, Educator.